(untitled) (L’uomo nero. Materiali per una storia delle arti della modernità, 2022)
The essay retraced the main stages of the relationship between Enrico Crispolti and Lucio Fontana, starting from the exhibition at L’Attico Gallery in Fall 1959 to the Catalogue Raisonné, begun after Fontana’s death and accomplished with the first edition in 1974. Crispolti summarized his point of view and critical perspective and proposed a retrospective gaze on Fontana creative itinerary from middle ‘20s, in order to highlight the nodal issues of artist’s imaginary. Finally, he reminded their tight dialogue during the last decade of Fontana’s life and career.